Gravity and Magnetic Interpretation to Study Deep Crustal Structures In Karbala and Surrounding Areas-Central Iraq - AL-Banna, Ahmed S.; Aziz, Aziz Farman (Iraqi Journal of Science, 2019)
Gravity and magnetic data were used to study the deep crustal structures in Karbala and surrounding areas in central Iraq. The space window method was used to separate the residual from regional anomalies of gravity and magnetic data, the spaces of window are equal to 48,36 and 24 km. The Total Horizontal Derivative (THD) techniques and local wavenumber of gravity and magnetic are used to identify the faults and their trends with the basement rocks. The N45W, N45E, N-S and rarely E-W trends of faults are detected in the basement rock. It is believed that some of these faults extending from the basement to the uppermost layer of the sedimentary rocks.